2015
DOI: 10.11648/j.abb.20150304.11
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Intercropping Soybean with Maize Under Two Maize Plant Distributions and Three Mineral Nitrogen Fertilizer Rates

Abstract: The advent of further bioengineering for growing soybean with maize holds only promise for the future of the crop intensification field. The present research studied responses of maize crop and its yield attributes to decrease mineral nitrogen (N) inputs by growing soybean with two maize plant distributions under three cropping systems. Local maize variety T.W.C. 310 was grown under intercropping and sole cultures in one row/ridge in one and two plants/hill spaced at 30 and 60cm, respectively, that received th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Nevertheless, they recorded the highest maize grains and soybean seeds (7650 and 1950 kg ha −1 , respectively) in mixed intercropping pattern. El-Shamy et al (2015) also observed that maize plants of mixed pattern have the highest nitrogen use efficiency (NUE) and ear leaf N content by improved underground conditions in rhizosphere. The maximum NUE in mixed pattern mainly due to plant density reached at 100% of sole cropping.…”
Section: Egyptmentioning
confidence: 92%
“…Nevertheless, they recorded the highest maize grains and soybean seeds (7650 and 1950 kg ha −1 , respectively) in mixed intercropping pattern. El-Shamy et al (2015) also observed that maize plants of mixed pattern have the highest nitrogen use efficiency (NUE) and ear leaf N content by improved underground conditions in rhizosphere. The maximum NUE in mixed pattern mainly due to plant density reached at 100% of sole cropping.…”
Section: Egyptmentioning
confidence: 92%
“…Introducing cowpea into the cropping systems not only addresses the problem of low soil fertility, but also increased protein in diets and green fodder utilization during summer. Legumes fix atmospheric nitrogen, which may be utilized by the legume and also excreted from the nodules into the soil and be used by other plants nearby (Shen & Chu, 2004;Sheahan, 2012) or compliment/supplement inorganic fertilizers (El-Shamy et al, 2015). Intercropped maize plants with cowpea, exhibited greater yield potential and resulted in higher growth, yield and yield components (Abdel-Wahab et al, 2016;Idoko et al, 2018;Toungos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, spacing is a practice that determines the spatial distribution of plants and affects canopy structure, light interception, and radiation use efficiency and, consequently, biomass or grain yield [16]. Although doubling maize number unit area −1 by increasing spacing between plants from 30 to 60 cm led to the similarity in plant density unit area −1 , there were significant increments in maize yield and its attributes under intercropping and sole culture [17]. Therefore, the objective of this investigation was to evaluate intercropping cowpea with suitable maize cultivar and its planting geometry for maximizing land usage and net return.…”
Section: Introductionmentioning
confidence: 99%